Effects of Preoperative Motor Status on Intraoperative Motor-evoked Potential Monitoring for High-risk Spinal Surgery: A Prospective Multicenter Study. Issue 12 (15th June 2021) - Kobayashi, Kazuyoshi; Imagama, Shiro; Yoshida, Go; Ando, Muneharu; Kawabata, Shigenori; Yamada, Kei; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; Tadokoro, Nobuaki; Takahashi, Masahito; et al.
Abstract : Study Design: Prospective multicenter observational study. Objective: To evaluate transcranial motor-evoked potentials (Tc-MEPs) baseline characteristics of lower limb muscles and to determine the accuracy of Tc-MEPs monitoring based on preoperative motor status in surgery for high-risk spinal disease. Summary of Background Data: Neurological complications are potentially serious side effects in surgery for high-risk spine disease. Intraoperative spinal neuromonitoring (IONM) using Tc-MEPs waveforms can be used to identify neurologic deterioration, but cases with preoperative motor deficit tend to have poor waveform derivation. Methods: IONM was performed using Tc-MEPs for 949 patients in high-risk spinal surgery. A total of 4454 muscles in the lower extremities were chosen for monitoring. The baseline Tc-MEPs was recorded immediately after exposure of the spine. The derivation rate was defined as muscles detected/muscles prepared for monitoring. A preoperative neurological grade was assigned using the manual muscle test (MMT) score. Results: The 949 patients (mean age 52.5 ± 23.3 yrs, 409 males [43%]) had cervical, thoracic, thoracolumbar, and lumbar lesions at rates of 32%, 40%, 26%, and 13%, respectively. Preoperative severe motor deficit (MMT ⩽3) was present in 105 patients (11%), and thoracic ossification of the posterior longitudinal ligament (OPLL) was the most common disease in these patients. There were 32 patients (3%) with no detectable waveform in any muscles, and these cases had mostly thoracic lesions. Baseline Tc-MEPs responses were obtained from 3653/4454 muscles (82%). Specificity was significantly lower in the severe motor deficit group. Distal muscles had a higher waveform derivation rate, and the abductor hallucis (AH) muscle had the highest derivation rate, including in cases with preoperative severe motor deficit. Conclusion: In high-risk spinal surgery, Tc-MEPs collected with multi-channel monitoring had significantly lower specificity in cases with preoperative severe motor deficit. Distal muscles had a higher waveform derivation rate and the AH muscle had the highest rate, regardless of the severity of motor deficit preoperatively. Level of Evidence: 3 Abstract : A prospective study of transcranial motor-evoked potentials (Tc-MEPs) in high-risk spinal surgery showed that patients with preoperative severe motor deficit had significantly lower specificity in Tc-MEPs monitoring. Distal muscles had a higher waveform derivation rate and the abductor hallucis had the highest rate, including in cases with preoperative severe motor deficit.